Journal of Sustainable Metallurgy - Blanpain, Bart.; Morita, Kazuki; Pal, Uday.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Journal of Sustainable Metallurgy is a peer-reviewed journal dedicated to presenting metallurgical processes and related research aimed at improving the sustainability of metal-producing industries, with a particular emphasis on materials recovery, reuse, and recycling. Its editorial scope encompasses new techniques, as well as optimization of existing processes, including utilization, treatment, and management of metallurgically generated residues. Articles on non-technical barriers and drivers that can affect sustainability will also be considered. The journal aspires to contribute in advancing the science but also to be a catalyst for tangible change toward more sustainable practices in the metallurgical industrial sector. (3z(BA journal of The Minerals, Metals & Materials Society(3y(B.s
Keywords: Sustainable development; Metals; Sustainable Development; Metallic Materials